2021
DOI: 10.1101/2021.04.06.438577
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Host Factor Rab11a is Critical for Efficient Assembly of Influenza A Virus Genomic Segments

Abstract: It is well documented that influenza A viruses selectively package 8 distinct viral ribonucleoprotein complexes (vRNPs) into each virion; however, the role of host factors in genome assembly is not completely understood. To evaluate the significance of cellular factors in genome assembly, we generated a reporter virus carrying a tetracysteine tag in the NP gene (NP-Tc virus) and assessed the dynamics of vRNP localization with cellular components by fluorescence microscopy. At early time points, vRNP complexes … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Further studies are needed to determine whether the same transport mechanism is active within TNTs and, conversely, whether Rab11a-actin dynamics may function in vRNP transport both within and between cells. Although Rab11a has been shown to be important for trafficking and efficient assembly of IAV genomes (2,8,12), we have shown that the loss of Rab11a does not completely abrogate genome assembly and viral particle release, indicating that there may exist an alternative pathway for canonical assembly of virions (12).…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…Further studies are needed to determine whether the same transport mechanism is active within TNTs and, conversely, whether Rab11a-actin dynamics may function in vRNP transport both within and between cells. Although Rab11a has been shown to be important for trafficking and efficient assembly of IAV genomes (2,8,12), we have shown that the loss of Rab11a does not completely abrogate genome assembly and viral particle release, indicating that there may exist an alternative pathway for canonical assembly of virions (12).…”
Section: Discussionmentioning
confidence: 70%
“…The intracellular transport of vRNP-Rab11a complexes is thought to occur via the microtubule network with the help of dynein motors (611), and disruption of this network by nocodazole has been shown to attenuate the generation of viral progeny (8). Similarly, our prior work revealed that loss of Rab11a reduces infectious viral titers, most likely due to a defect in the packaging of vRNPs, leading to the formation of incomplete viral particles (12). Taken together, these data demonstrate the importance of an intact microtubule network as well as Rab11a in the IAV life cycle.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…Other alternatives to modulate the material properties tailored for function can be developed. For example, accumulating evidence shows that blocking viral inclusion formation hinders viral infection (Amorim, 2019; Amorim et al, 2011; de Castro Martin et al, 2017; Eisfeld et al, 2011; Han et al, 2021; Momose et al, 2011; Vale-Costa et al, 2016; Vale-Costa and Amorim, 2017; Veler et al, 2022). Herein, we observe that increase in temperature biases the system to dissolving viral inclusions, therefore activating exothermic reactions close to IAV inclusions may lead to their dissolution.…”
Section: Discussionmentioning
confidence: 99%